The Effect of Parents' Education Level and Learning Motivation on Student's Biology Learning Achievement Class XI SMA Negeri I Panai Hulu - Linda Safitri; Zunaidy Abdullah Siregar (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of parental education level and learning motivation on biology learning achievement of class XI students of SMA Negeri I Panai Hulu. This type of research uses multiple regression analysis studies and was carried out at SMA Negeri I Panai Hulu with a purposive sampling technique for class XI MIPA 1 with 35 students, XI MIPA 2 with 36, and XI MIPA 5 with 31 students. The results showed Calculation of hypothesis testing using the Chi-Square test obtained a significant value of 0.000 less than 0.05. Parents' Education Level and Learning Motivation Influence on Student Achievement in Class XI SMA Negeri I Panai Hulu Year.